FPGA implementation of OFDM-based PSDU encoding and decoding for IEEE 802.11a - Montalbo, Bermie Lyn Q.; Volante, Maria Katrina E. (2011)
The demand for high data rate wireless multimedia applications has increased significantly in the past few years. This has spurred the development of numerous wireless communication techniques that are both power and bandwidth efficient. An example of which is orthogonal frequency division multiplexing (OFDM). OFDM is a multi-carrier modulation method that divides the signal bandwidth into parallel subcarriers or narrow strips of bandwidth. It offers high bandwidth efficiency, robustness to narrowband interference, and a relatively simple digital implementation. Several standards have been released that specify OFDM as its modulation and multiplexing technique, one of which is the IEEE 802.11a. This project is an implementation of an OFDM-based PSDU encoding and decoding for IEEE 802.11a on a Xilinx Virtex-5 Field Programmable Gate Array (FPGA). The transceiver, implemented on baseband, was modeled and simulated using Xilinx System Generator, a development tool for FPGAs built on top fo MATLAB Simulink. Performance analysis of the hardware implementation as compared with the purely software implementation was also carried out. Simulation results show that, in terms of bit error rate (BER), the software implementation generally performs better that its hardware counterpart, although differences in the values are only minimal.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Orthogonal frequency division multiplexing; IEEE 802.11 (Standard); Radio -- Transmitter-receivers.